Marburg virus reaches Rwanda: how close are we to a vaccine solution? - Olivier Sibomana; Clyde Moono Hakayuwa; Jildas Munyantore (International Journal of Infectious Diseases)
Marburg virus disease (MVD) is a highly virulent and often fatal disease caused by the Marburg virus, a member of the Filoviridae family, closely related to the Ebola virus. Historically, outbreaks have been sporadic but lethal across various African countries, with high case fatality rates (CFRs). In 2023, significant outbreaks occurred in Tanzania and Equatorial Guinea, with CFRs of 62.5% and 75%, respectively. In 2024, Rwanda faced its first outbreak, starting on September 27, 2024. By November 8, 2024, Rwanda had conducted 7,408 tests, confirming 66 cases, 15 of which were fatal, and 51 recoveries. Although no approved vaccine currently exists for MVD, global health authorities are prioritizing the development of effective vaccines. Drawing on insights from the rapid COVID-19 vaccine development, several promising candidates are under exploration, with the cAd3-MARV showing notable potential. This paper examines the current MVD outbreak in Rwanda and the progress toward developing a long-term vaccine solution.